SEFEKTIVITAS PROGRAM BIMBINGAN KETERAMPILAN BAGI PENYANDANG TUNAGRAHITA DI YAYASAN PEMBINAAN ANAK CACAT (YPAC) MEDAN - Purba, Geby Claudia; Siregar, Hairani (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
Children as the nation's next generation need to receive serious attention because the progress and decline of a country will greatly depend on the current and future generations. If children do not receive their rights and social protection as one of the pillars of the nation, they will tend to experience problems or become problems in the family and community. In reality, not all children are born with the physical conditions of children in general. There are those who have had disabilities since birth or have had disabilities during development. Children with disabilities in every interaction with others require special services that are different from children in general so that children with disabilities are identified with children with special needs. Several types of children with special needs, one of which is the mentally retarded. Mentally retarded children or often called people with intellectual disabilities, are conditions where children have below average intellectual abilities. Children with intellectual disabilities in achieving independence need to develop their potential through skills, mental and social guidance. One of the social development foundations that is directly involved in providing skills guidance for people with intellectual disabilities is the Medan Foundation for the Development of Disabled Children (YPAC) with skills guidance classes, namely: culinary skills, beauty skills, batik skills, computer skills and entrepreneurial skills. This research aims to determine the effectiveness of the skills guidance program for mentally retarded people at the Medan Foundation for the Development of Disabled Children (YPAC). The key informant in this research was the principal of the SLB C (Retardant) school at YPAC Medan, the main informants were class teachers/supporter and children with intellectual disability and additional informants were parents/guardians of children with intellectual disability. Data collection techniques were carried out using literature study, observation, interviews and documentation. The data obtained in the field was analyzed qualitatively to obtain the conclusion that the skills guidance program for people with intellectual disabilities at the Medan Foundation for the Development of Disabled Children (YPAC) was effective using four indicators of effectiveness, namely: accuracy of program targets, program socialization, program objectives and program monitoring.